INTEGRATING ENVIRONMENTAL POLLUTION ISSUES INTO SCIENCE LEARNING TO ENHANCE STUDENTS' ENVIRONMENTAL LITERACY: A LITERATURE REVIEW - Nindy Notrilauvia; Yulia Fitri Harahap; Edo Nofriadi; Intan Lestari Mulyaning Tyas (Universe, 2026)
Environmental pollution has become an increasingly important context in science education because it enables students to connect scientific concepts with authentic environmental challenges. Integrating environmental pollution issues into science learning is considered a promising approach to fostering students' environmental literacy and promoting sustainability-oriented education. This study aims to synthesize existing research on the integration of environmental pollution issues into science learning and examine its contribution to the development of students' environmental literacy. A literature review was conducted by analyzing relevant national and international publications focusing on pollution-based science learning, scientific literacy, environmental literacy, and education for sustainable development. The findings indicate that integrating environmental pollution issues into science learning enhances students' environmental literacy, scientific literacy, critical thinking skills, and environmentally responsible behavior. Student-centered instructional approaches, including problem-based learning, inquiry-based learning, socio-scientific issues, and sustainability-oriented learning, consistently provide more meaningful and reflective learning experiences. Furthermore, environmental pollution issues function not only as science content but also as authentic learning contexts that encourage critical reflection, environmental awareness, and sustainability-oriented decision-making. Despite these benefits, challenges remain in teachers' pedagogical readiness, instructional implementation, and the integration of sustainability perspectives into science classrooms. This review highlights the importance of contextualizing environmental pollution issues within science learning as an effective strategy for promoting environmental literacy and advancing sustainability-oriented.